The Hermeneutics of vrkh: Septimal Structures, Alien Significations, and the Meaning of Creation in the Book of Job - Mcgrew, Israel (The catholic biblical quarterly, 2025)
The Book of Job's sevenfold use of the term [inline-graphic 02] ("to bless" or "to curse") in the prose sections has been observed but not sufficiently analyzed. As Job challenges the goodness and integrity of creation and as creation is understood to be the culmination in a septimal blessing in Genesis 1 (a source for the poet), this structure merits serious study. After addressing issues of historical authorship, I argue that the structure helps us relate the prose and the poetry. Since the term occurs six times in Job's prologue (chaps. 1-2), the poetry prolongs the indetermination of the septimal cycle, structurally and dramatically underscoring the problem of evil's challenge to God's creative vision. Since the plot is driven by how Job will [inline-graphic 02] God—literally as bless or euphemistically as curse—Job's performance in the poetry is portrayed as a necessary condition for fulfilling God's creative vision and vindicating it against the sāṭān's hermeneutic. However, since the septimal structure is concluded by God's final act of blessing Job (42:10), the structure implies that, given Job's qualified success in the story, creation must finally be restored and perfected through God's final redemption of his servant Job.